ZACHARY SOLOMON’S AGGRESSIONS IN ACHIEVING APOTHEOSIS DEPICTED IN DAN BROWN’S THE LOST SYMBOL - FAIDAH, IRNA NUR (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Aggression, Apotheosis, Hierarchy of Needs, The Lost Symbol, Self-Actualization, Zachary Solomon The basic concept of self-actualization is that people tend to be the best that they can be. This phenomenon is also portrayed in Dan Brown’s The Lost Symbol. The Lost Symbol deals with a character named Zachary Solomon who wants to transform into status of God or it is called as apotheosis. In achieving the apotheosis, Zachary Solomon should satisfy his needs according to Abraham Maslow’s hierarchy of needs which are divided into physiological needs, safety needs, love and belongingness, self-esteem, and self-actualization.On the process to achieve the apotheosis, Zachary Solomon does several actions if he thinks someone tries to hamper his goal. His actions often hurt others.  Psychologically, his actions indicate an aggression. In relation with this phenomenon the writer conducts a study about Zachary Solomon’s aggression in achieving the apotheosis as depicted in Dan Brown’s The Lost Symbol. The research employs psychological approach, Maslow’s hierarchy of needs and aggression theory.It results that Zachary Solomon does several kinds of aggression toward some people whom he thinks as his obstacle in achieving his apotheosis. It shows that most of aggressions which were done by Zachary Solomon were caused by situational factors, however the social-learning mechanism also becomes one of the factor of his aggression.In the end, it is expected that this research helps others who want to do research related to material object and psychological field, especially for self-actualization and aggression. It is suggested also for other researchers to analyze any other psychological problem that is faced by Zachary Solomon in The Lost Symbol.